Development of an experimental model for assessing the effects of cigarette smoke and virus infections on inflammatory responses to bacterial antigens. Issue 6 (August 2014) - Moscovis, Sophia; Hall, Sharron; Burns, Christine; Scott, Rodney; Blackwell, Caroline
Interactions among major risk factors associated with bacterial infections were assessed in a model system using surrogates for virus infection; IFN-g, and exposure to cigarette smoke; cigarette smoke extract (CSE), nicotine and cotinine. Cytokine responses elicited by LPS from THP-1 cells in the presence of these components, or combinations of components, were assessed by multiplex bead assay, i.e. IL-1β, IL-6, IL-8, IL-10, TNF-α and IFN-γ. IFN-γ-priming significantly increased pro-inflammatory cytokines induced by LPS. CSE suppressed production of pro-inflammatory cytokines IL-1β, TNF-α and IFN-γ, but enhanced production of IL-8. Nicotine and cotinine suppressed all cytokine responses. In combination, IFN-γ masked the inhibitory effects of CSE. In relation to the objectives of the study, we concluded that (a) IFN-γ at biologically relevant concentrations significantly enhanced pro-inflammatory responses; (b) CSE, nicotine and cotinine dysregulated the inflammatory response and that the effects of CSE were different from those of the individual components, nicotine and cotinine; (c) when both IFN-γ and CSE were present, IFN-γ masked the effect of CSE. There is a need for clinical investigations on the increase in IL-8 responses in relation to exposure to cigarette smoke and increased pro-inflammatory responses in relation to recent viral infection.